2009
DOI: 10.3168/jds.2009-2140
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: Use of meta-analysis in animal health and reproduction: Methods and applications

Abstract: The objectives of this paper are to provide an introduction to meta-analysis and systematic review and to discuss the rationale for this type of research and other general considerations. We highlight methods used to produce a rigorous meta-analysis and discuss some aspects of interpretation of meta-analysis drawing on examples from the animal and veterinary science literature. Meta-analysis is a rapidly expanding area of research that has been relatively underutilized in animal and veterinary science. It is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
190
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(192 citation statements)
references
References 84 publications
1
190
0
1
Order By: Relevance
“…To avoid this potential bias, data not available to the public domain (e.g., industry reports) as well as unindexed reports (e.g., conference proceedings) were also included in this meta-analysis. In addition to articles indexed in electronic databases, a hand search of references in review papers as well as communication with scientists, manufacturing companies, and industry partners, who have been working in the relevant field, are all considered important methods for a comprehensive search (Lean et al, 2009). It may Figure 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid this potential bias, data not available to the public domain (e.g., industry reports) as well as unindexed reports (e.g., conference proceedings) were also included in this meta-analysis. In addition to articles indexed in electronic databases, a hand search of references in review papers as well as communication with scientists, manufacturing companies, and industry partners, who have been working in the relevant field, are all considered important methods for a comprehensive search (Lean et al, 2009). It may Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…not be possible to find every relevant study on a topic, but pursuing multiple avenues to find as many relevant studies as possible can minimize publication bias and increase the precision of the pooled estimates of effect while providing meaningful results of most importance to decision makers (Lean et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, results from a single experiment will not provide a definitive understanding of the effect of SR treatment because the conditions under which observations are made in a single experiment are inevitably narrow (Sauvant et al, 2008). A meta-analysis approach (Glass, 1976), summarising the results across published studies in a particular area and in combination with new statistical techniques, allows increased precision of analysis of effects across multiple experiments (St-Pierre, 2001;Sauvant et al, 2008;Lean et al, 2009). In a historical review of SR experiments, Journet and Demarquilly (1979) reported that an SR increase of one cow/ha resulted in a mean reduction in milk production per cow of 10%, but an increase in production per ha of over 20%.…”
Section: Introductionmentioning
confidence: 99%
“…Metaanalyses summarize and combine information, weight and analyse the results of independent studies relating to a specific topic. Hence by increasing the sample size and statistical power the precision of an estimated outcome can be increased (Lean et al, 2009 (Gugiu et al, 2010). This appraisal should address aspects like enrolment criteria, the allocation in experimental designs, blinding, the sample size, statistical methodologies and the objectiveness in the discussion of the results.…”
Section: The Hierarchy Of Evidencementioning
confidence: 99%